Clinical profile and outcome of pediatric heart surgeries at semi-urban tertiary care cardiac center of Gujarat, India: a 54-month single-center retrospective chart review - Tandon, Rahul; Bhende, Vishal V.; Kumar, Amit; Dhedhi, Naresh; Patel, Mamta R.; Tandon, Krutika Rahul (Frontiers in Pediatrics, 2025)
ContextThe most common congenital condition, congenital heart disease (CHD), is often left untreated or doesn't get timely attention for various reasons. Nowadays, many pediatric cardiac centers in India offer surgical management, even in semi-urban or rural areas. Our center is one of them.AimsThis study aims to generate regional data from the Western part of India, primarily to determine the outcome of patients who had surgical intervention at our pediatric cardiac center.Methods and materialThe present study retrospectively analyzed the data of the operated pediatric patients by reviewing the charts of patients admitted to the pediatric division of the cardiac center between April 2018 and October 2022. All demographic details, anthropometry, preoperative evaluation, operative procedures, postoperative issues, outcomes, etc. were reviewed, and the collected data were entered into Microsoft Excel.Statistical analysisDescriptive statistics were used to present demographic data. Chi-square and Fisher exact tests were applied to find an association, and a p-value of <0.05 was considered statistically significant.ResultsOut of the 422 pediatric admissions during the period studied, 386 underwent cardiac surgeries. The median (Q1, Q3) age of patients in months was 12 (6, 60), and 251 (61.2%) were males. The most prevalent CHD was ventricular septal defect (VSD), accounting for 88 patients (21.6%). Out of the 386 total patients who underwent cardiac surgery, 16 (4.1%) patients experienced mortality. The most common surgeries performed were VSD closure, patent ductus arteriosus ligation, and intracardiac repair for tetralogy of Fallot (TOF).ConclusionsPediatric heart surgery was offered for a varied CHD with comparable mortality and morbidity with other centers.